2008
DOI: 10.1128/aac.00421-08
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of l -Arginine in Adults with Moderately Severe Malaria

Abstract: Severe malaria is associated with decreased nitric oxide (NO) production and low plasma concentrations of L-arginine, the substrate for NO synthase. Supplementation with L-arginine has the potential to improve NO bioavailability and outcomes. We developed a pharmacokinetic model for L-arginine in moderately severe malaria to explore the concentration-time profile and identify important covariates. In doses of 3, 6, or 12 g, L-arginine was infused over 30 min to 30 adults with moderately severe malaria, and pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
46
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(47 citation statements)
references
References 34 publications
(44 reference statements)
1
46
0
Order By: Relevance
“…Intravenous infusion of L-arginine has been used to reduce pathology associated with severe malaria, but this application is invasive and expensive and requires medical monitoring (39,68). However, oral supplementation has been used to enhance livestock production (40)(41)(42)(43) and to treat clinical cases of trauma and sepsis (44).…”
Section: Discussionmentioning
confidence: 99%
“…Intravenous infusion of L-arginine has been used to reduce pathology associated with severe malaria, but this application is invasive and expensive and requires medical monitoring (39,68). However, oral supplementation has been used to enhance livestock production (40)(41)(42)(43) and to treat clinical cases of trauma and sepsis (44).…”
Section: Discussionmentioning
confidence: 99%
“…Tregs inhibit the Th1 response by modifying DC function, producing IL-10, and inducing CD4 + T cell apoptosis (Slade and Langhorne 1989;Zheng et al 2009), which facilitates immune evasion by the parasite (Hisaeda et al 2004). Previous studies have shown that Tregs contributed to determining the incidence and outcome of CM in Pb ANKA-infected mice by altering the balance of pro-(IFN-γ, TNF-α, IL-6, IL-17, and NO) and anti-inflammatory (IL-10) responses (Lopansri et al 2003;Amante et al 2007;Yeo et al 2008b). Therefore, we assessed the effect of L-Arg on the percentage of Tregs and the production of the anti-inflammatory cytokine IL-10.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, they did find good evidence for the protective role of NO in human CM (Lopansri, Anstey et al 2003;Gramaglia, Sobolewski et al 2006;Weinberg, Lopansri et al 2008). Some investigators proposed that severe malaria is associated with reduced NO production and low blood levels of L-arginine, the substrate for NO synthase (Yeo, Rooslamiati et al 2008). Cell-free hemoglobin produced by hemolysis in falciparum malaria quench NO, disrupt endothelial function, increase adhesion receptor expression and impair www.intechopen.com tissue perfusion (Yeo, Lampah et al 2009).…”
Section: Arginine/nitric Oxide Signaling Pathwaymentioning
confidence: 99%
“…Cell-free hemoglobin produced by hemolysis in falciparum malaria quench NO, disrupt endothelial function, increase adhesion receptor expression and impair www.intechopen.com tissue perfusion (Yeo, Lampah et al 2009). Adjunctive agents to improve endothelial NO bioavailability including L-arginine are being extensively tested in human patients (Yeo, Lampah et al 2007;Yeo, Lampah et al 2008;Yeo, Rooslamiati et al 2008;Yeo, Lampah et al 2009) and a safety pharmacokinetics profile has been established (Yeo, Rooslamiati et al 2008).…”
Section: Arginine/nitric Oxide Signaling Pathwaymentioning
confidence: 99%